Հայերէն հնատիպ մի նորայայտ տպագրութիւն - Տէր-Վարդանեան, Գէորգ; Մատար, Աննա Մարիա (Մատենադարան)
While researching the Armenian old printing books of the Royal Library of The Hague, Anna Maria Mattaar found an unknown 4-page text in a copy of the Psalms published in the printing house of Ghukas Vanandetsi in 1714–1715 in Amsterdam. The text is not related to the Psalms. It is a circular "Letter of Exhortation" (“T‘ught‘ hordorakan”) published in the same printing house in 1714, which urges the addressees to participate in the fundraising for building the Armenian Church of the Holy Spirit in Amsterdam. The authors are “Babajan, son of Sultanum, and Nikoghos, son of Theodoros,” the trustees, overseers and agents of the construction of the church. Since a unique copy of this printed document is preserved and it witnesses to an important page in the life of the Dutch-Armenians, namely the construction of the Church of the Holy Spirit, the "Letter of Exhortation" is published here together with a photographic reproduction. For the history of Armenian printing, it is very important to search in archives, supply bibliographic information and, if necessary, republish such texts related to everyday issues, printed in small numbers and often not spread outside the places of printing. Исследуя армянские старопечатные книги Гаагской Королевской библиотеки, Анна Мария Маттаар в одном экземпляре Псалтири, изданной в 1714-1715 гг. в Амстердамской типографии Гукаса Ванандеци, обнаружила не связанное по содержанию с Псалтирью неизвестное издание. Это состоящее из четырех страниц циркулярное “Наставительное письмо”, вышедшее из той же типографии в том же 1714 г. и призывающее адресатов принять участие в сборе средств, необходимых для строительства армянской церкви Святого Духа в Амстердаме. Авторами этого циркуляра были попечители, смотрители и подрядчики строительства церкви, “Бабаджан, сын Султанума” и “Никогос, сын Теодороса”. Учитывая тот факт, что этот печатный документ сохранился в единственном экземпляре, а также его роль в жизни голландских армян и истории строительства церкви Святого Духа, “Наставительное письмо” публикуется как в виде текста, так и в фотографическом воспроизведении. Для истории армянского книгопечатания в целом очень важно разыскивать в архивах, библиографически обрабатывать и при необходимости публиковать подобные издания, посвященные повседневным вопросам, размноженные небольшим тиражем и часто не выходившие за пределы мест их напечатания.
Keywords: Հնատիպ տպագրութիւն; Նորահայտ տպագրութիւն